LITERASI PENDIDIKAN ERA REVOLUSI INDUSTRI 4.0 - Danim, Sudarwan (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Illiteration consists of two types, that are traditional illiteration and modern illiteration. Traditional illiteration is those who cannot read, write, and count. Modern illiteration or illiteracy of the 21st century is people who cannot learn, stop learning, and cannot relearn. The literacy of education is essentially how one must understand the essence of the process of taking education and the negative effects that result from failing to implement and implement it. Modern civilization gave birth to demands for technological literacy, in the form of one's ability to provide, use, manage, evaluate, and understand technology. Education is the heart of preparing for the current and future generations to continue to develop, and to further develop human potential rather than pitting sheep with machines. The current generation's journey is in the Industrial Revolution 4.0 (IR 4.0), which is characterized by artificial intelligence, automation, cellular supercomputers, intelligent robots, self-driving cars, improved neuro-technology brains, genetic editing, online learning, online student and employee recruitment, and other. There are three main things so that humans can "defeat" machines which are the key to creating future jobs, namely creative efforts, social interaction, and physical dexterity and mobility.